Financial Management: How Banking Systems Support SMEs Sustainability (Literature Review) - Hariyanti, Hariyanti; Wahyu Putra, Christophorus Indra; Yusuf, Muhammad; Suhendra, Agus; Subagio, Mochammad (Greenation Research & Yayasan Global Resarch National, 2024)
Relevant articles on financial management The scientific article How Banking Systems Support SME Sustainability is a review of the literature within the field of financial management science. The purpose of this paper is to develop a hypothesis regarding the connection between elements, which can be applied to more financial management research. Descriptive qualitative methodology is applied in this work. Previous research that are still pertinent to this one provided the data used in this one. Academic media, credible journals, and academic platforms including Scopus Elsevier journals, Emerald, WoS, DOAJ, EBSCO, SINTA, GARUDA, and digital books (e-books) provided the data for this study. This study's conclusions are that SME sustainability and financial management are influenced by the banking system.